Giant Sublingual Epidermoid Cyst (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Epidermoid and dermoid cysts represent less than 0.01% of all oral cavity cysts. The cysts can be defined as epidermoid when the lining presents only epithelium, dermoid cysts when skin adnexa are found, and teratoid cysts when other tissue such as muscle, cartilage, and bone are present. In this article, we present a case of sublingual epidermoid cyst with a submental component in a 15 years old girl. She presented with complaints of a mass in the oral cavity, difficulty in speaking, dysphagia, progressive snoring during sleep, occasional shortness of breath and cosmetic problems for last 6 months. A mass displacing the tongue superiorly and posteriorly was noticed in oral cavity and a firm diffuse swelling was also noticed in the submental area, extending down to the thyroid notch. The differential diagnosis includes infectious process, ranula, lymphatic malformation, tumours etc. FNAC revealed preoperative diagnosis of an epidermoid cyst . Under general anesthesia a submental horizontal incision was made and the mass was excised completely. Histopathological examination of the mass confirmed diagnosis of an epidermoid cyst. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20984 J Bangladesh Coll Phys Surg 2013; 31: 159-161